Qibla direction verification of Arau Royal Old Tomb using : UAV technique / Muhizee Sahat - Sahat, Muhizee (2018)
The rapid development in the design, research and production of various types of Unmanned Aerial Vehicle has an influence on a wide range of application and fields. UAV offers the rapid data collection and can avoid hazardous environment without risk of human and others. This study conducted to verify the qibla direction at the Arau Royal Old Tomb, Perlis by using the UAV Technique. The aerial photographs were obtained at the surrounding old tomb area using Phantom 3 Standard camera and the both of control points and verification points were obtained from the GPS observations. All the data obtained at the tomb area including the established qibla direction from the Perlis’ Mufti Department and DSMM were used to produce the orthophoto. The orthophoto then been used for qibla direction verification and old graves qibla direction checking. Each deflection then been tabulated for easier reading and the Arau Royal Old Tomb then been mapped containing two qibla direction which are the new and the old. In conclusion, this study has achieved all the proposed objectives and proves that UAV system can be used for qibla direction verification and checking for Islamic graves.